Alveolar epithelial glycocalyx shedding aggravates the epithelial barrier and disrupts epithelial tight junctions in acute respiratory distress syndrome - Jun Li (Biomedicine & Pharmacotherapy, 2021)
The main pathophysiological mechanism of acute respiratory distress syndrome (ARDS) invovles the increase in alveolar barrier permeability that is primarily caused by epithelial glycocalyx and tight junction (TJ) protein destruction. This study was performed to explore the effects of the alveolar epithelial glycocalyx on the epithelial barrier, specifically on TJ proteins, in ARDS. We used C57BL/6 mice and human lung epithelial cell models of lipopolysaccharide (LPS)-induced ARDS. Changes in alveolar permeability were evaluated via pulmonary histopathology analysis and by measuring the wet/dry weight ratio of the lungs. Degradation of heparan sulfate (HS), an important component of the epithelial glycocalyx, and alterations in levels of the epithelial TJ proteins (occludin, zonula occludens 1, and claudin 4) were assessed via ELISA, immunofluorescence analysis, and western blotting analysis. Real-time quantitative polymerase chain reaction was used to detect the mRNA of the TJ protein. Changes in glycocalyx and TJ ultrastructures in alveolar epithelial cells were evaluated through electron microscopy. In vivo and in vitro, LPS increased the alveolar permeability and led to HS degradation and TJ damage. After LPS stimulation, the expression of the HS-degrading enzyme heparanase (HPA) in the alveolar epithelial cells was increased. The HPA inhibitor N-desulfated/re-N-acetylated heparin alleviated LPS-induced HS degradation and reduced TJ damage. In vitro, recombinant HPA reduced the expression of the TJ protein zonula occludens-1 (ZO-1) and inhibited its mRNA expression in the alveolar epithelial cells. Taken together, our results demonstrate that shedding of the alveolar epithelial glycocalyx aggravates the epithelial barrier and damages epithelial TJ proteins in ARDS, with the underlying mechanism involving the effect of HPA on ZO-1.